Soon to be married Filipino men's knowledge, perceptions and attitudes toward family planning - Tizon, Cara Denise L.
This is a descriptive exploratory study that determined the family planning knowledge, perceptions and attitudes of the soon to be married Filipino men. A total of 100, 25 35 year old males who were engaged to be married and registered at the Quezon City Halls Family Planning and Marriage Seminar participated in the survey, while another 30 participated in the focus group discussions. Data obtained were classified into their emergent themes and summarized into frequency tables. Results showed that the respondents knowledge, perceptions and attitudes toward family planning are congruent with one another. They perceived family planning to be a confluence of several factors. primarily birth control as it relates to well being, parenthood and finances. Attitudes regarding the concept of family planning were very positive despite the lack of information on the subject. The implementation of an effective family planning policy as well as providing comprehensive family planning education were found to be necessary in order to actively involve men in their and their parents family planning concerns.